The Effect Of Advance Organizer Assisted By The Project To Student’s Generic Life Skills In The Material Of The Human Excretion System - Dessy Nurjanah; Jujun Ratnasari; Suhendar Suhendar (Universitas Negeri Padang, 2019)
This research is based on the problems the generic life skills of students who are still low. The effort that can be done is to apply the Advanced Organizer learning model assisted by project in the excretion system material at SMAN 3 Sukabumi. The purpose of this research is to find out the influence of Advance Organizer learning model assisted by project on generic life skills of students of SMAN 3 Sukabumi. The type of research used quasi-experiment with Nonequivalent control group design. In this study the sampling technique used purposive sampling. The samples in this study were grades XI8 and XI5. The instruments used test questions, attitude scale, observation sheet and response questionnaire. The results of data analysis showed that the average N-gain test scores of experimental class 0.77 and a control class 0.47. The average attitude scale of the experimental class 80% and the control class 83%. The average observation sheet of the experimental class 91% and the control class 73%. The average response questionnaire of the experimental class to material 89%, to learning model 83% and to generic life skills 84%. Based on the prerequisite test data the results of the study were normally distributed and homogeneous. The result of research by hypothesis testing with the Z-test show Zhitung=8 > ZTabel=1,96 then H0 is rejected and H1 is accepted. The conclusion is that the Advanced Organizer learning model assisted by projects has an influence on students' generic life skills.Keywords: Advanced Organizer assisted by the project, generic life skills